The deployment of IPv6 SIP-based VoIP applications. (2nd August 2006) - Chen, Whai-En
This paper presents an IP version 6 (IPv6) Session Initiation Protocol (SIP)-based Voice over IP (VoIP) deployment in Taiwan. This deployment supported by National Information and Communication Initiative (NICI) IPv6 R&D and Promotion divisions contains the SIPv6 User Agents (UAs), Socket-layer Translator, SIPv6 Translator and SIPv6 Translator. The major contributions of this paper are introducing the IPv6 translation mechanisms for SIP-based applications and exercising the ENUM on IPv6 SIP networks, to establish the communications between the SIP-based VoIP and the Public Switched Telephone Network (PSTN) users.